Shorter Contributions to Alaskan Trace Elements Studies, Part 1: Trace Elements Reconnaissance in the Candle Creek Area, Fairhaven District, Seward Peninsula, Alaska - Gault, H. R. (Geological Survey (U.S.), 1949)
Report discussing the U.S. Geological Survey's investigation of radioactive element samples found in the Candle Creek area on the Seward Peninsula of Alaska.